Pengaruh Kompetensi Guru Terhadap Produktivitas Sekolah Pada Sekolah Dasar Islam Terpadu Di Kecamatan Klari Karawang - Sri Haryati Dewi; Nitta Kanya; Fajar Eryanto Septiawan (Pusat Riset dan Inovasi Nasional, 2025)
The school productivity of each institution needs to be considered in order to create optimal graduate results. School productivity needs to be considered because it affects the growth and development of the institution. Therefore, this study was conducted where in the observation there were problems, especially at the Integrated Islamic Elementary School in Klari District, Karawang. The research method used is descriptive method and verification method. Population of 240 teachers, sample of 150 teachers, Non Probability sampling technique, based on sample provisions by Slovin, data collection technique questionnaire